Pro-inflammatory cytokines serve as communicating molecules between the liver and brain for hepatic encephalopathy pathogenesis and Lycium barbarum polysaccharides protection. (10th February 2020) - Sun, Xiaoming; Lv, Yi; Huang, Lu; Gao, Hao; Ren, Chaoran; Li, Jingjing; Bie, Man; Li, Wei; Koike, Kazuo; So, Kwok-Fai; Xiao, Jia
Abstract: Ethnopharmacological relevance: Gogi berry is a traditional food supplement and medical herbal which has been widely used in Eastern Asian countries. Lycium barbarum polysaccharides (LBP) are the major active components of Gogi berry and have been proved to possess a lot of biological activities. Aim of the study: We aimed to delineate the protective effect and mechanism of LBP on hepatic encephalopathy (HE). Materials and methods: We investigated the protective mechanism of LBP in a thioacetamide (TAA, intraperitoneally injected, 400 mg/kg) induced acute HE mice model. Key phenotypes of clinical HE were phenocopied in the mice model, including high mortality, severe hepatic histology injury, increased hepatic oxidative stress, apoptosis, enhanced circulating levels of pro-inflammatory cytokines and ammonia, suppressed tryptophan hydroxylase activity, and deficits in locomotor activity. Results: The pathological alterations were effectively ameliorated by the oral administration with LBP (5 mg/kg, oral gavage, everyday), which were mediated by regulating MAPK pathways in both the liver and brain. Knockout of pro-inflammatory cytokines TNF-α or IL-6 effectively ameliorated impaired mice locomotor activity and MAPK activation in the brain. In an in vitro TNF-α-, IL-6-, or ammonia-induced microglia damaged cell model, cell injuries were evidently protected by the co-administration with LBP (50 μg/ml). Conclusion: LBP ameliorated the hepatic/brain injuries and impaired locomotor activities in a HE mice model. Pro-inflammatory cytokines may serve as communicating molecules linking the liver and brain for the HE pathogenesis, partly through MAPK regulation. Graphical abstract: Hepatic encephalopathy is a neuropsychiatric disease caused by severe liver damages or failure. In the present study, we found that LBP ameliorate HE symptoms by attenuating the pro-inflammatory cytokine production and disturbed MAPK pathway in the liver and brain. TNF-α and IL-6 may serve as communicating molecules linking the liver and brain for the HE pathogenesis, partly through MAPK regulation. Image 1